2017
DOI: 10.1039/c7cc01813d
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-mediated radical insertion/cyclization cascade reaction: synthesis of phenanthridines and isoquinolines from isocyanides

Abstract: A visible-light promoted single electron oxidation of ether enabled by photoredox catalysis has been accomplished. This procedure initiates a novel radical insertion/cyclization cascade reaction to generate phenanthridines and isoquinolines from easily available isocyanides under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The mechanistic studies revealed that this reaction goes through a visible light-mediated single electron transfer mechanism. Initially, the irradiation of [Ru- She and co-workers in 2017 disclosed [69] a simple and effective visible light-mediated route to prepare phenanthridine derivatives 188 a via single electron oxidation of ethers by using photoredox catalyst under the mild conditions. Different types of phenanthridine derivatives can be afforded with moderate to good yields by the photoredox catalyzed activation of the sp 3 CÀ H bond of ethers followed by the radical insertion/ cyclization cascade reaction (Scheme 78).…”
Section: Visible Light-mediated Ruthenium Catalyzed Reactionsmentioning
confidence: 99%
“…The mechanistic studies revealed that this reaction goes through a visible light-mediated single electron transfer mechanism. Initially, the irradiation of [Ru- She and co-workers in 2017 disclosed [69] a simple and effective visible light-mediated route to prepare phenanthridine derivatives 188 a via single electron oxidation of ethers by using photoredox catalyst under the mild conditions. Different types of phenanthridine derivatives can be afforded with moderate to good yields by the photoredox catalyzed activation of the sp 3 CÀ H bond of ethers followed by the radical insertion/ cyclization cascade reaction (Scheme 78).…”
Section: Visible Light-mediated Ruthenium Catalyzed Reactionsmentioning
confidence: 99%
“…Wide range of functional groups shows good tolerance under the optimized reaction conditions (Scheme 246). [38g] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%
“…The iminyl radical 127 undergoes CÀ C β-scission to afford cyanoalkyl radical 128, which adds to the isocyanide 1 In addition to Ir-mediated alkylated strategies, visible-light mediated Ru-catalysed single-electron oxidation of ethers was achieved by She and coworkers (Scheme 29). [68] It is a cascade reaction involving radical insertion followed by cyclization to afford phenanthridine and isoquinoline derivatives 134, 135. In this strategy, Ru(II) complex gets converted to its excited state upon visible light irradiation.…”
Section: Arylating Reagentsmentioning
confidence: 99%